The Influence of Leadership and Competence on Employee Commitment and Performance of Employees of The Education and Culture Department of Meranti - Nurafni, Nurafni; Indarti, Sri; Efni, Yulia (Indonesian Journal of Economics, Social, and Humanities, 2025)
This study aims to determine and analyze the influence of leadership and competence on organizational commitment. To know and analyze the influence of leadership and competence on employee performance. To know and analyze the effect of organizational commitment on employee performance and to know and analyze the influence of leadership and competence on performance through organizational commitment. In this study, the population was 105 non-educational employees. The sample used was 105 people. The data used in this study were primary data and secondary data, while the data collection technique used questionnaires. The data analysis technique used in this study is the data analysis used in this study is sem. Leadership influences commitment. Competence affects commitment. Leadership affects employee performance. Competency affects the performance of employees. Commitment has a significant effect on employee performance. Leadership has a significant effect on employee performance through commitment. And competence has a significant effect on employee performance through commitment.